Hepatic arterial infusion chemotherapy combined with lenvatinib and PD-1 inhibitors versus lenvatinib and PD-1 inhibitors for unresectable HCC: a meta-analysis - Wei, Min; Zhang, Pengwei; Yang, Chaofeng; Li, Yang (Frontiers in Oncology, 2024)
ObjectivesThis study aimed to evaluate the effectiveness of combining hepatic arterial infusion chemotherapy (HAIC) with lenvatinib and programmed cell death protein 1 (PD-1) inhibitors in the treatment of advanced, unresectable hepatocellular carcinoma (HCC).MethodsA comprehensive search across multiple databases was conducted to identify relevant studies published up to May 2024. This search focused on clinical trials investigating the combination of HAIC with lenvatinib and PD-1 inhibitors for the treatment of advanced HCC. Data from these trials were analyzed using either fixed-effects or random-effects models, with results reported as hazard ratios (HRs) or risk ratios (RRs) with 95% confidence intervals (CIs). To evaluate the robustness of the findings, trial sequential analysis was employed.ResultsA total of 8 cohort studies encompassing 1073 patients with unresectable HCC were included. Compared with other treatment regimens, the combined use of HAIC, lenvatinib, and PD-1 inhibitors significantly improved overall survival (OS) (HR=0.53 [95% CI 0.45, 0.63], P<0.00001), progression-free survival (PFS) (HR 0.56 [95% CI 0.46, 0.61], P<0.0001), the objective response rate (ORR) (RR=1.82 [95% CI 1.52, 2.18], P<0.00001), and the disease control rate (DCR) (RR=1.24 [95% CI 1.16, 1.33], P<0.00001). Trial sequential analysis (TSA) results indicated that the existing data were sufficient for making quantitative conclusions about the ORR and DCR.ConclusionCombining HAIC with lenvatinib and PD-1 inhibitors enhances the effectiveness of treatment for unresectable HCC. This approach is particularly beneficial for patients who have a high tumor burden or those who are refractory to transarterial chemoembolization (TACE), providing a more effective solution for these challenging cases.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024575853, identifier CRD42024575853.